NILAI-NILAI AKHLAK DALAM SERI KOMIK ISLAMI DUNIA SEMENTARA TERTAWALAH SEPERLUNYA (ANALISIS SEMIOTIK) - Raisa Maya Agustin (Komunitas Dosen Dakwah Institut Agama Islam Negeri (IAIN) Palu, 2018)
Comics are one of the media that can be used to convey religious messages. Islamic comic series, Dunia Sementara Tertawalah Seperlunya, is a compilation comic that packs religious messages, especially messages about morals. The message is packed with light language and humor. This study aims to find out and explain the moral values ​​contained in the World Islamic comic series Dunia Sementara Tertawalah Seperlunya. This study uses a qualitative approach with a type of qualitative content analysis research. Data analysis using semiotics Charles Sanders Peirce model that focuses on the triangle of meaning to analyze the contents of the research subject. Data collection using documentation. The results of the research in this comic contain five moral values, namely morals towards Allah, Morality to the Messenger of Allah., Personal morals, morality in the family, and morality in society. (1) Moral values ​​towards Allah shown cautiously; (2) Moral values ​​towards the Prophet. shown by loving, glorifying, and following and obeying the Prophet. which is realized by relying on the hadith in choosing a mate; (3) Personal moral values ​​are indicated by courage (syajā’áh) and forgiveness; (4) Moral values ​​in the family are shown by the attitude of sharing love and love, getting along with each other well between wife and husband, and education - direction for children; and (5) Inner moral values ​​are shown by helping each other (ta’āwun), visiting and receiving guests well, and answering greetings.